The Behavior of Nanovesicles of Physicochemical Profiles: Compose of β-Cyclodextrin and Cisplatin for Anti-Tumor Activity and Decrease Toxicity Affected Normal Surrounding Tumor Tissues - Panyosak, Atchara (Trends in Sciences, 2023)
CP (cisplatin) was entrapped in lipid bilayer and β-CD-CP (β-cyclodextrin-CP) was entrapped in hydrophilic bilayer both were prepared by chloroform film method with sonication. The entrapment efficiency of CP-LPS (CP-Liposome) and β-CD-CP-LPS were 83.44 and 82.20 %, respectively, two-tailed t-test and no significant difference at the confidence interval, p < 0.05. Size distribution of CP-LPS and β-CD-CP-LPS were investigated by DLS were in range 322 and 1033 nm, respectively. CP release from CP-LPS or β-CD-CP-LPS exposed to physiological conditions as PBS at 37 °C. CP from both LPS formulations have showed an initial burst release around < 17 and < 10 %, respectively. CP-LPS and β-CD-CP-LPS maintained as plateau phase of both for four days and seven days, respectively. CP-LPS showed % cumulative controlled release CP of CP-LPS and β-CD-CP-LPS were about 15 - 16 and 10 - 11 %, respectively. CP-LPS and β-CD-CP-LPS released until 83.6 % for six days and 82 % for eight days, respectively. CP released from CP-LPS and β-CD-CP-LPS were in a controlled deportment for 10 days. β-CD-CP-LPS, CP molecules bound β-CD was exhibited in dynamic equilibrium with free drug molecules which ascribes the controlled release behavior of β-CD-CP-LPS to quietly release and prolong action, diminish dose of toxicity of cancer drug that effected to normal tissues that surrounding tumor tissue. β-CD was oligosaccharides,an attracted tumor, tumor snatch themselves as nutrient consume more than the normal tissues. Thus, β-CD-CP-LPS and low dose of normal dose of CP can damage cancer cells. This synergistic effect was saved for normal cells which surrounding tumor tissue. HIGHLIGHTS Nanovesicles (NVs) are a particularly attractive delivery system because of their NVs’ size, which permits carrying across biological membranes and exact target sites by a probable surface adjustment, sustained release delivers, and diminished drug dose to treat. The experiment found that β-CD-CP-LPS transported to HeLa cells in a sustained release to prolonged action. β-CD-CP-LPS, CP molecules bound within the β-CD are in dynamic equilibrium with free drug molecules, which ascribes the controlled release behavior of β-CD-CP-LPS to quietly released and long term which diminished toxicity that effected to normal tissues which surrounding tumor tissue. Moreover, β-CD was an oligosaccharide, an attracted tumor. Tumors snatch themselves as nutrient consume more than the normal Thus, β-CD-CP-LPS and a low dose of normal dose of CP can damage cancer cells. This cooperative effect was saved for normal cells which surround tumor tissue. GRAPHICAL ABSTRACT